Narrative writing : grades 3-5 - Trischitta, Andrea; Buehler, Stephanie (Westminster, CA : Teacher Created Materials, 2000)
Activities include lessons on the elements of narrative writing, figurative language, grammar, proofreading/editing skills, and ways to use technology.
Keywords: Narration (Rhetoric) -- Problems, exercises, etc; English language -- Composition and exercises -- Study and teaching (Elementary); Language arts (Elementary)